Explore the Historical Context of Chinese Hip-hop/Rap Music: Construction of Chinese Blackness Field, Dialect Rap, and 'Keepin' it Real' of Mainstream Official Upsurg - HungTing Tang (International Society of Philosophy and Cosmology, 2024)
This dissertation, borrowing the concepts of Popular Music Studies, Black Studies, and Global Hip hop studies, aims to explore the discursive authenticity of 'Keepin' It Real' in Mainland China Hip Hop/Rap Music. It has been set a Hip hop 'wave' and became a popular culture styling after the network program "Rap of China" was on air in AiQiYi. But before the program streamed, Hip Hop culture has been already appearances in China Society by the 'black culture', 'street style', 'underground', and 'fashion' which articulated through trans popular music industries. In this essay is mainly discussion the development of China Hip hop/Rap with the authenticity 'Keepin' It Real' before the Rap of China was on air. And use chronicle to contextualization the historical process of its blackness being accepted and transformed in China. In this process, started by the intermediary of foreigners, to the creation of using 'dialect' rap music by local teenagers, presents the narrative basis of the 'Keepin' it Real' of China hip-hop culture / rap. Finally, reflect on how the mainstream media industries could continue to create the 'real' appearance of China hip-hop culture/rap through the tripartite reconciliation by local cultural practice, commercial media wrapping and government intervention.